Protective Effects of Resveratrol on TNF-α-Induced Endothelial Cytotoxicity in Baboon Femoral Arterial Endothelial Cells - Juan Xiao; Jun Song; Vida Hodara; Allen Ford; Xing Li Wang; Qiang Shi; Li Chen; John L. VandeBerg (Journal of Diabetes Research)
Endothelial injury induced by inflammatory factors plays a critical role in the pathogenesis of cardiovascular disease. Endothelial cell (EC) apoptosis, proliferation, migration, and cellular adhesion molecule (CAM) expression contribute to the development of atherosclerosis. We investigated the effects of resveratrol (0.1–100 μM) on the proliferation, migration, and CAM expression of primary cultures of baboon arterial endothelial cells (BAECs). In addition, we tested its effects under normal conditions as well as under inflammatory conditions induced by tumour necrosis factor-α (TNF-α) administered either by cotreatment, pretreatment, or posttreatment. Immunocytochemistry, MTT, wound-healing, and flow cytometry assays were performed. The resveratrol treatment significantly enhanced BAEC proliferation and attenuated TNF-α-induced impairment of proliferation at the optimal doses of 1–50 µM. Resveratrol at a high dose (100 μM) and TNF-α impaired BAEC migration, while low doses of resveratrol (1–50 μM) attenuated TNF-α-induced impairment of BAEC migration. Moreover, resveratrol inhibited TNF-α-induced ICAM-1 and VCAM-1 expression. Taken together, our results suggest that the resveratrol protects BAECs after inflammatory stimulation as well as ameliorates inflammatory effects at low concentrations. Consequently, resveratrol should be considered as a candidate drug for the prevention and treatment of inflammatory vascular diseases.